1982
DOI: 10.1097/00006254-198210000-00004
|View full text |Cite
|
Sign up to set email alerts
|

How Women View Postepisiotomy Pain

Abstract: Episiotomy is one of the most commonly performed operative procedures and yet little information is available on the subjective reactions in the puerperium to this procedure. The present study was designed to furnish information on the attitudes of patients, levels of pain, and of course recovery by studying a consecutive series of 101 Caucasian primiparea who received episiotomies at delivery. Women were interviewed within 24 hours of delivery and then, at three months after delivery, completed a questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
14
1
5

Year Published

1983
1983
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 0 publications
5
14
1
5
Order By: Relevance
“…Even Reading et al (1982) state that a large number of stitches increase the pain. All women in both groups reported some experienced pain, but the E p group represents a higher level of discomfort (Tables IV-VI) which agrees with the findings of other authors (Kitzinger & Walters 1981;Reading et al 1982, Harrison et al 1984 but not with the results of Sleep et al (1984) who found no differences between the groups. At the follow-up after three weeks the Ep group had a lower rate of healing and the reported discomfort during sitting and walking was higher.…”
Section: Nssupporting
confidence: 90%
See 1 more Smart Citation
“…Even Reading et al (1982) state that a large number of stitches increase the pain. All women in both groups reported some experienced pain, but the E p group represents a higher level of discomfort (Tables IV-VI) which agrees with the findings of other authors (Kitzinger & Walters 1981;Reading et al 1982, Harrison et al 1984 but not with the results of Sleep et al (1984) who found no differences between the groups. At the follow-up after three weeks the Ep group had a lower rate of healing and the reported discomfort during sitting and walking was higher.…”
Section: Nssupporting
confidence: 90%
“…Episiotomy (Ep) is the most common operative procedure during delivery (Pritchard & McDonald 1980, Reading et al 1982, Thacker & Banta 1983. A high frequency of postepisiotomy discomfort and pain has been reported in several studies (Buchan & Nicholls 1980, Kitzinger & Walters 1981Reading et al 1982, Thacker & Banta 1983, Sleep et al 1984, Isager-Sally et al 1986). There are many studies about Ep which document undesirable side effects with almost no evidence that the operation has any benefits.…”
Section: Introductionmentioning
confidence: 99%
“…Some women circled moderate or severe pain and sensory pain increased if it was related to an episiotomy, a similar finding to Reading et al (1982). We could speculate that increased pain with episiotomy may be due to dissatisfaction with pain relief for episiotomy, which is in alignment with MaClean et al (2000) or to the degree of perineal laceration, which would be similar to that recorded in a larger cohorts (Eisenach et al, 2008;Francisco et al, 2011).…”
Section: Discussionsupporting
confidence: 72%
“…6 Strategies to reduce perineal trauma and the appropriate repair of any perineal damage sustained are important for avoiding and alleviating pain. Factors that may influence the severity of pain experienced include mode of birth, 7 degree of perineal trauma, 8 type of suture material 9,10 and perineal repair technique. 11,12 The provision of safe and effective pain relief for perineal trauma using rectal analgesia is one of several therapies used in clinical practice, which also include oral analgesics, local anaesthetics, therapeutic ultrasound and non-pharmacological applications such as baths and ice packs.…”
Section: Introductionmentioning
confidence: 99%